Asuhan Keperawatan Pada Tn.R Dengan Diabetes Melitus Tipe I di Ruang Aster RSUD Dr.CHasbullah Abdulmadjid Kota Bekasi - Waldan Andriana; Yuanita Panma (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2019)
Diabetes mellitus (DM) is a group of metabolic disorders characterized by increased blood glucose levels (hyperglycemia) due to damage to insulin secretion, insulin action or both. Diabetes mellitus can cause complications in hypoglycemia and diabetic ketoacidosis, while chronic complications can include coronary heart disease, cerebrovascular disease, peripheral vascular disease, diabetic retinopathy, diabetic neuropathy and diabetic nephropathy. The client is named Mr. R, male, aged 25 years with a medical diagnosis of type 2 diabetes mellitus. After the assessment, a nursing diagnosis was obtained, namely ineffective airway clearance associated with retained secretion, the risk of fluid volume deficiency associated with excess gastric loss: diarrhea, risk of changes in nutrition less than the body's needs associated with nausea, insufficiency of insulin, acute pain associated with hyperperistaltic and high risk of spread of infection to sepsis associated with high glucose levels, effects of invasive procedures: infusion installation, pre-existing respiratory infections. The results achieved after performing nursing care are three nursing diagnoses that have been overcome ie ineffective airway clearance associated with retained secretions, the risk of lack of fluid volume associated with excess gastric loss: diarrhea and acute pain associated with hyperperistaltic. In addition, there is 1 (one) nursing diagnosis that is partially resolved, namely the risk of changes in nutrition less than the body's needs related to nausea, insufficiency of insulin and there is 1 (one) nursing diagnosis that has not been resolved, namely the high risk of spread of sepsis associated with high glucose levels, effects invasive procedure: infusion installation, respiratory infections that existed before.